Influence of strategic management practices on the entrepreneurial orientation of South African firms in the financial and business services sector - Murumbika, McEdward (My University, 2012)
In this dissertation, strategic management and corporate entrepreneurship are combined in a single empirical research investigating the influence of business strategic management practices on organisational entrepreneurial orientation. Understanding this relationship has progressively become crucial in today’s hypercompetitive global environment where businesses, regardless of national location, size, age and industry, are facing incessant and dynamic change. Specifically, the influence of strategic management practices on corporate entrepreneurship in medium to large corporations in the financial and business services sector in South Africa is analysed by testing hypotheses that predict the relationship between strategic management dimensions of locus of planning, scanning intensity, planning flexibility, planning horizon, and strategy control attributes, and entrepreneurial orientation. By applying factor, cluster and multiple regression statistical analyses, the study made four key findings. First, the results confirm that selected dimensions of strategic management practices influence the entrepreneurial orientation of firms. This in turn effect the position a firm occupies along a conceptual conservative-entrepreneurial continuum. Second, the study indicates that firms with perceived higher entrepreneurial orientation exhibit better performance measures. This finding supports the thesis that entrepreneurial orientation is an integral component for business performance in attaining sustainable competitive advantage, achieving above-average earnings and wealth creation. Third, a methodology that combined strategic management and corporate entrepreneurship in a single research generated new knowledge confirming that entrepreneurial orientation is a key construct in both subdisciplines. Fourth, the results show that divergent organisational entrepreneurial orientation profiles help in classifying firms along the entrepreneurial continuum. Furthermore, the research made a provisional finding that there are four possible distinct and excusive clusters of business groups along the conservative-entrepreneurial continuum in determining corporate entrepreneurial orientation in organisations
Keywords: Entrepreneurship; Strategic planning; South Africa